Sistem Pendukung Keputusan Pemilihan Supplier Dengan Metode AHP Pada Apotek & Laboratorium Klinik Interna Berbasis Web - Awanda Octavianti Putri; Eka Prasetyaningrum (STMIK Budi Darma, 2021)
Inventory of products or goods in the form of medicines and others is one of the work activities. In procuring products, in this case drugs, the selection of drug suppliers is very important for a drugstore business, pharmacy or regional hospital. Interna Pharmacy & Clinical Laboratory is a private pharmacy located in Sampit, East Kotawaringin, Central Kalimantan. The problem that exists at the Internal Pharmacy & Clinical Laboratory is the selection of suppliers by comparing several suppliers or only based on the thoughts of the owner, pharmacist or pharmacist assistant. Suppliers are selected based on price, number of discounts given, speed of delivery of goods, completeness of drugs and drug packaging. Selection of suppliers with a system that has been running with various criteria resulted in the selection of suppliers is not accurate and takes time. Based on the problems above, it is very necessary to have a decision support system website using the Analytical Hierarchy Process method. By using a decision support system with the Analytical Hierarchy Process method, the Pharmacy & Internal Clinical Laboratory can make an assessment by comparing each criterion. The output of this research is a decision support system using the Analytical Hierarchy Process method. This study aims to make it easier to select drug suppliers from various criteria, save time in selecting drug suppliers, get good suppliers for the procurement of the necessary drugs